ETHICAL ISSUES IN THE USE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Mirzaraximov Mirzaraxim Aminjon o’g’li (World Scientific Research Journal, 2025)
Artificial intelligence (AI) is quickly changing education. It affects how we teach, learn, and manage schools. But, AI brings ethical issues like bias and data privacy. We also need to think about transparency, who is responsible when AI makes mistakes, and if AI will replace teachers. This study looks at different sources to find the main ethical problems with using AI in education. We used a method to study many online articles and papers. AI can make learning personal and schools more efficient. However, these ethical problems could decrease trust and fairness. We discuss ways to handle these problems. We also suggest what future studies and rules should focus on.